MODIFIKASI PERILAKU TEKNIK POSITIVE REINFORCEMENT DENGAN MEDIA PAPAN ATENSI UNTUK MENINGKATKAN KEDISIPLINAN PPKS DI SENTRA WIRAJAYA MAKASSAR - Zainuddin, Kurniati; Marzuki, Wirdayanti; Atikah, Ummul; Saputra, Yogi Bambang; Gazali, Wiwik (LPPM Institut Pendidikan Nusantara Global, 2022)
Behavior modification is a technique for changing behavior or reaction to a stimulus by strengthening adaptive behavior or eliminating maladaptive behavior. The behavior modification technique used is positive reinforcement which is carried out through “Papan Atensi” which contain various routine activities of 9 social welfare service recipients (PPKS) Sentra Wirajaya Makassar. Samples were randomly selected using cluster random sampling technique. Behavior modification aims to see changes in PPKS disciplinary behavior at Sentra Wirajaya Makassar by using an attention board media which contains various routine activities of 9 PPKS people in one of the male houses. The results of the behavior modification that has been done show that there is an increase in PPKS disciplinary behavior after being given positive reinforcement.